White Matter Microstructure Associations of Cognitive and Visuomotor Control in Children: A Sensory Processing Perspective - Brandes-Aitken, Annie; Anguera, Joaquin A.; Chang, Yi-Shin; Demopoulos, Carly; Owen, Julia P.; Gazzaley, Adam; Mukherjee, Pratik; Marco, Elysa J. (Frontiers in Integrative Neuroscience, 2019)
Objective: Recent evidence suggests that co-occurring deficits in cognitive control and visuomotor control are common to many neurodevelopmental disorders. Specifically, children with sensory processing dysfunction, a condition characterized by sensory hyper/hypo-sensitivity, show varying degrees of overlapping attention and visuomotor challenges. In this study, we assess associations between cognitive and visuomotor control abilities among children with and without sensory processing dysfunction. In this same context, we also examined the common and unique DTI tracts that support the overlap of cognitive control and visuomotor control. Method: We collected cognitive control and visuomotor control behavioral measures as well as diffusion tensor imaging (DTI) data in 37 children with SPD and 25 typically developing controls (TDC). We constructed regressions to assess for associations between behavioral performance and mean fractional anisotropy (FA) in selected regions of interest. Results: We observed an association between behavioral performance on cognitive control and visuomotor control. Further, our findings indicated that FA in the anterior limb of the internal capsule, the anterior thalamic radiata, and the superior longitudinal fasciculus support both cognitive control and visuomotor control, while FA in the superior corona radiata uniquely correlate with cognitive control performance and FA in the posterior limb of the internal capsule and the cerebral peduncle tract uniquely correlate with visuomotor control performance. Conclusions: These findings suggest that children who demonstrate lower cognitive control are also more likely to demonstrate lower visuomotor control, and vice-versa, regardless of clinical cohort assignment. The overlapping neural tracts, which correlate with both cognitive and visuomotor control suggest a possible common neural mechanism supporting both control-based processes.